Эндотелиальные дисфункции при посттравматической эпилепсии = Endothelial dysfunction in post-traumatic epilepsy - I. V. Savitskiy; A. A. Myronov; I. V. Miastkovskaja (Kazimierz Wielki University, 2016)
Savitskiy I. V., Myronov A. A., Miastkovskaja I. V. Эндотелиальные дисфункции при посттравматической эпилепсии = Endothelial dysfunction in post-traumatic epilepsy. Journal of Education, Health and Sport. 2016;6(6):245-252. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55357 http://ojs.ukw.edu.pl/index.php/johs/article/view/3573   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016.   ЭНДОТЕЛИАЛЬНЫЕ ДИСФУНКЦИИ ПРИ ПОСТТРАВМАТИЧЕСКОЙ ЭПИЛЕПСИИ ENDOTHELIAL DYSFUNCTION IN POST-TRAUMATIC EPILEPSY   И. В. Савицкий, А. А. Миронов, И. В. Мястковская I. V. Savitskiy, A. A. Myronov, I. V. Miastkovskaja   Одесский национальный медицинский университет, Одесса, Украина Odessa National Medical University, Odessa, Ukraine   Abstract The aim of this study was to design a method for determining endothelial dysfunction in post-traumatic epilepsy experiment using Vilenbrant factor activity, INR, 2.3 dyfosfohlitseratu red blood cells, interleukin 1 β enabling a high degree of accuracy to detect the presence of endothelial dysfunction and the degree of hypoxia in each case and can be used for early diagnosis of hypoxia in patients with PTE, which will prevent additional ischemic brain injury patients and negative effects of hypoxia. The problem is solved by the proposed activity in animals reveal Vilenbrant factor, INR, 2.3 dyfosfohlitseratu red blood cells, interleukin 1 β modeled after TBI and after the introduction konvulsantu (pikrotoksynu) and at values above indicators above the threshold established between endothelial dysfunction and epileptic focus formation. Today there is no experimental model that provides research of the problem of endothelial dysfunction in TBI and its relationship with the formation of epileptic focus. The data that will be receiving through the study of this problem will assist with TBI treatment. Also, using these data will be found new approaches to disease prevention in PTE patients.   Key words: endothelial dysfunction, post-traumatic epilepsy, experiment, traumatic brain injury, brain.